Diversity within the pRb pathway: is there a code of conduct? - Munro, S; Carr, S; La Thangue, N (2012)
The failure of cell proliferation to be properly regulated is a hallmark of tumourigenesis. The retinoblastoma protein (pRb) pathway represents a key component in the regulation of the cell cycle and tumour suppression. Recent findings have revealed new levels of complexity reflecting a repertoire of post-translational modifications that occur on pRb together with its key effector E2F-1. Here we provide an overview of the modifications and consider the possibility of a 'code' that endows pRb with the ability to function in diverse physiological settings.